Research on the Application of Expressive Art Therapy in the Teaching of Mental Health Education Courses for College Students - SONG, XUE (Pacific International Journal, 2023)
Mental health education courses hold a pivotal role in nurturing the psychological well-being of college students and shaping their future development. This paper explores the integration of expressive art therapy into mental health education courses and its impact on college freshmen's mental health and classroom satisfaction. Drawing on a non-random cluster sampling method, 198 students from a university in Shandong Province participated, with half forming the experimental expressive art group and the other half constituting the control traditional group. Results demonstrated that the expressive art group experienced significant improvements in mental health, with higher scores in self-affirmation and lower scores in anxiety and depression compared to the control group. The study emphasizes a student-centered approach, focusing on experiential learning and self-expression, facilitated through music, painting, and psychodrama. It also highlights the role of expressive arts therapy in reducing self-defense mechanisms, enhancing selfexpression, and challenging negative cognitions. While the study shows promise, future research should consider longterm effect and qualitative assessments to comprehensively evaluate the clinical significance of expressive art group therapy.